Tantangan Bagi Cinta Tanah Air Ancaman dan Peran Buzzer Terhadap Persatuan Bangsa Pada Era Internet of Things (IoT) - Zulisih Maryani; Katon Krisnandaru; Erika Nur Widiastuti; Vemi Rahmayani; Axelle Chandra; Vellen Oktaviara; Zahra Aprilia Putri; Syavira Dwi Ramadhani; Ari Ardhana Abriansyah (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
The phenomenon of buzzers has become a significant issue in the dynamics of Indonesia’s digital society, particularly in the new media era. Buzzers, both individuals and groups, are utilized to shape public opinion through social media for commercial and political purposes. In this of shaping public opinion context, buzzers not only function as disseminators of information but also as actors who construct public perception through structured narratives, including the spread of biased information and misinformation. This study aims to analyze the impact of buzzer activities on Indonesians’ sense of patriotism within the digital space. The research employs a qualitative descriptive approach using content analysis of various social media contents, supported by relevant literature studies. The analysis focuses on identifying narrative patterns created by buzzers and their implications for national attitudes. The findings indicate that buzzer-generated narratives tend to be polarizing and oriented toward specific group interests, potentially triggering fragmentation in public opinion. The sense of patriotism in the digital context is analyzed through several indicators, including support for national unity, the ability to filter information (digital literacy), participation in disseminating positive national content, and critical attitudes toward provocative narratives. Exposure to biased buzzer content is found to influence public perspectives and may weaken social cohesion. This study contributes to the academic discourse by examining the relationship between buzzer activities and the expression of digital nationalism through a qualitative approach, which has previously been largely discussed conceptually. It also highlights the importance of strengthening digital literacy and social media regulation as strategic efforts to maintain national unity.